Urbane Bekenntnisse. Starke Gesten setzen. - Molitor, Reimar (Müller u. Busmann, 2014)
Interview mit Reimar Molitor, Geschäftsführer des Region Köln/Bonn e.V.
Keywords: Regionalplanung; Kooperation; Koordination; Kommunale Zusammenarbeit; Stadtentwicklung; Stadtregion; Regionalwirtschaft; Standortpolitik